2007
DOI: 10.1159/000127382
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Carcinoid Tumours: Indolent but Not Benign

Abstract: Background: The aim of this retrospective study was to analyse the malignant behaviour of low-grade pulmonary neuroendocrine tumours (NETs) treated at our institution. Patients and Methods: We reviewed 48 consecutive patients with pulmonary NETs referred to our Medical Oncology Unit between 1998 and 2006, including 33 subjects with typical carcinoids (TCs) and 15 with atypical carcinoids (ACs). Results: At diagnosis, there were 37 metastatic and 11 non-metastatic patients. Medical treatments used were somatost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 65 publications
(45 reference statements)
1
10
0
Order By: Relevance
“…In our study, survival was very good in these endocrine tumor cases, however, it varies in the adult population when separated based on histologic type of carcinoid. Adult patients with typical pulmonary carcinoid have a similar prognosis with 5-y survival of 93%, however atypical histology portends a much worse prognosis of 73% [21]. Other studies have shown similar results, and report dismal prognosis with additional subtypes, such as large cell neuroendocrine carcinoma [22].…”
Section: Discussionmentioning
confidence: 72%
“…In our study, survival was very good in these endocrine tumor cases, however, it varies in the adult population when separated based on histologic type of carcinoid. Adult patients with typical pulmonary carcinoid have a similar prognosis with 5-y survival of 93%, however atypical histology portends a much worse prognosis of 73% [21]. Other studies have shown similar results, and report dismal prognosis with additional subtypes, such as large cell neuroendocrine carcinoma [22].…”
Section: Discussionmentioning
confidence: 72%
“…Somatostatin receptors are often overexpressed on the surface of low-grade lung NETs (27). SSAs bind to the somatostatin receptor, blocking the release of peptides and amines, and thus help to control symptoms.…”
Section: Treatment Modalities For Advanced Low Grade Netmentioning
confidence: 99%
“…Peptide receptor radioligand therapy specifically delivers a radiolabeled agent to a target, such as somatostatin receptors which often overexpressed on the surface of metastatic lung NETs (27). PRRT using yttrium Y-90 labeled octreotide was first used to treat this disease in the early 1990 and has been delivered and used in many centers for decades, despite the lack of phase III trials confirming benefit.…”
Section: Treatment Modalities For Advanced Low Grade Netmentioning
confidence: 99%
“…4 Radiotherapy has a limited role in the treatment of these tumours and is mostly indicated for non-resectable and palliative cases only.…”
Section: Long Answermentioning
confidence: 99%